Trade and Transboundary Pollution - Brian R. Copeland; M. Scott Taylor (American Economic Review, 1995)
This paper examines how national income and trading opportunities interact to determine the level and incidence of world pollution. We find that (i) free trade raises world pollution if incomes differ substantially across countries; (ii) if trade equalizes factor prices, human-capital-abundant countries lose from trade, while human-capital-scarce countries gain; (iii) international trade in pollution permits can lower world pollution even when governments' supply of permits is unrestricted; (iv) international income transfers may not affect world pollution or welfare; and (v) attempts to manipulate the terms of trade with pollution policy leave world pollution unaffected.